Hubungan Status Gizi dengan Profil Indeks Eritrosit Pasien Anak di Instalasi Rawat Inap Rumah Sakit Umum Bahagia Makassar - Amini, Fakhiratunnisa; Jalaluddin, Syatirah; Fauziah, Henny; Irnawati, Risma; Syamsuddin, Darussalam (Medical Scope Journal, 2025)
Abstract: World Health Organization (WHO) reports that more than 30% of children experience weight loss, 15% are underweight, and more than 75% of children are overweight. Iron is one of the most important nutrients for erythrocyte production. Low erythrocyte level makes the body unable to meet its nutritional needs in general and to supply oxygen to all organs and tissues. This study aimed to evaluate the relationship between nutritional status and erythrocyte index profile of pediatric patients at inpatient installation of Rumah Sakit Bahagia in 2023. This was a quantitative and analytical study with a cross-sectional approach. Samples consisted of 98 pediatric inpatients selected by using purposive sampling technique. This study used secondary data, namely medical records. The Spearman Rho test analyzed the relationship between the nutritional status and erythrocyte indexes, and obtained p-values, as follows: p=0.005 for MCV; p=0.367 for MCH; and p=0.046 for MCHC. In conclusion, there is no significant relationship between nutritional status and MCH and MCHC, but there is a significant relationship between nutritional status and MCV. Keywords: nutritional status; erythrocyte index; pediatric patients Abstrak: World Health Organization melaporkan bahwa lebih dari 30% anak mengalami penurunan berat badan, 15% mengalami kekurangan berat badan, dan lebih dari 75% anak mengalami kelebihan berat badan. Zat besi merupakan salah satu nutrisi terpenting untuk produksi eritrosit. Kadar eritrosit yang rendah membuat tubuh tidak dapat memenuhi kebutuhan nutrisinya secara umum dan pasokan oksigen ke organ dan jaringan tubuh terganggu. Penelitian ini bertujuan untuk mengevaluasi hubungan antara status gizi dengan profil indeks eritrosit pasien anak di instalasi rawat inap Rumah Sakit Bahagia tahun 2023. Desain penelitian ialah analitik kuantitatif dengan pendekatan potong lintang. Sampel berjumlah 98 pasien anak yang dipilih menggunakan teknik purposive sampling. Penelitian ini menggunakan data sekunder yaitu rekam medik. Hasil uji Spearman Rho terhadap hubungan antara status gizi dengan indeks eritrosit mendapatkan p=0,005 untuk MCV; p=0,367 untuk MCH; dan p=0,046 untuk MCHC. Simpulan penelitian ini ialah tidak terdapat hubungan bermakna antara status gizi dengan MCH dan MCHC, namun terdapat hubungan bermakna antara status gizi dengan MCV. Kata kunci: status gizi; indeks eritrosit; pasien anak